Alterations in photosynthesis and energy reserves in Galdieria sulphuraria during corn stover hydrolysate supplementation. (September 2019) - Mozaffari, Khadijeh; Seger, Mark; Dungan, Barry; Hanson, David T.; Lammers, Peter J.; Holguin, F. Omar
Abstract: The carbon allocation and alterations in the photosynthetic apparatus of the red microalga, G aldieria sulphuraria CCMEE 5587.1 were investigated under photoautotrophic, mixotrophic and heterotrophic conditions in this paper. Photosynthetic O2 evolution values and chlorophyll a content decreased during one week of cultivation in both hetero- and mixotrophic cultivations. A 2.1-fold and 2.6-fold reduction was observed in phycocyanin content under mixo- and heterotrophic conditions, respectively. TEM microscopy confirmed that mixotrophic conditions favor carbon allocation toward starch biosynthesis along with an increase in the size of chloroplasts. In contrast, carbon is allocated toward lipid production under heterotrophic cultivation with apparent smaller multi-lobed chloroplasts. These results increase our understanding of the roles of photosynthesis and external carbon sources on bioenergy products from Galdieria . Graphical abstract: Unlabelled Image Highlights: Galdieria sulphuraria readily metabolizes all monomeric sugars mixo- and heterotrophically. Growth on corn stover hydrolysate leads to decreased photosynthesis mixotrophically. Chloroplasts of heterotrophically grown cells contained smaller multi-lobed chloroplasts. A higher carbon flux to starch and fatty acids were exhibited mixo- and heterotrophically.